E-waṃ Khaṅ-sar Mkhan Rin-po-che Ṅag-dbaṅ-yon-tan-rgya-mtshor gsol ba ʼdebs pa thar paʼi sgo ʼbyed ces bya ba bźugs so - Ṅag-dbaṅ-blo-gros-sñiṅ-po, Ṅor Khaṅ-gsar, 1876-1952 (s.n., 1972)
Devotional verses addressed to Ṅag-dbaṅ-yon-tan-rgya mtsho, 70th abbot of Ngor of the Khansgar Labrang.